2018
DOI: 10.3174/ajnr.a5595
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Early Ischemic Changes with the Latest-Generation Flat Detector CT: A Comparative Study with Multidetector CT

Abstract: Determination of ASPECTS on flat detector CT is feasible, showing no significant difference compared with multidetector CT ASPECTS and a similar predictive value for functional outcome. Our findings support the use of flat detector CT for emergency stroke imaging before mechanical thrombectomy to reduce door-to-groin time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
(34 reference statements)
1
13
0
1
Order By: Relevance
“…These findings are consistent with our quantitative image analysis that showed that our new XperCT protocol had a significantly higher signal to noise ratio (2.08 +/-0.64 vs. 1.15 +/-0.27) compared to the standard XperCT protocol. Our findings are also consistent with other groups' findings that early ischemic changes can be detected with newer generation CBCT imaging [20].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with our quantitative image analysis that showed that our new XperCT protocol had a significantly higher signal to noise ratio (2.08 +/-0.64 vs. 1.15 +/-0.27) compared to the standard XperCT protocol. Our findings are also consistent with other groups' findings that early ischemic changes can be detected with newer generation CBCT imaging [20].…”
Section: Discussionsupporting
confidence: 93%
“…And 5) Is there (and what is the extend of the) infarct core? For question 1 and 2, there is growing evidence that latest generation FDCTs are able to reliably exclude ICH [ 20 , 21 ] as well as can reliably be used for the determination of ASPECTS [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current DTAS imaging protocols are based largely on the use of FP-CT with rotational C-arm systems (Figure). FP-CT offers the possibility to perform cross-sectional imaging, although it is still inferior to conventional multislice CT. 28 Noncontrast FP-CT can be used to detect the presence of ICH with a very high sensitivity comparable to that of multislice CT. 29 The latest-generation FP-CT allows detection of a large infarct core 30 with a significant reduction of artifacts. 31 The main difference between DTAS protocols published by different research groups lies in the use of FP-CTA with IV contrast (Table ).…”
Section: Imaging Protocols For Dtasmentioning
confidence: 99%